Structural basis of the cysteinyl leukotriene receptor type 2 activation by LTD4 - Mengting Jiang; Youwei Xu; Xiaodong Luan; Kai Wu; Zhen Li; H. Eric Xu; Shuyang Zhang; Yi Jiang; Wanchao Yin (Proceedings of the National Academy of Sciences, 2025)
The G protein–coupled cysteinyl leukotriene receptor CysLT2R plays intricate roles in the physiology and pathogenesis of inflammation-related processes. It has garnered increasing attention as a potential therapeutic target for atopic asthma, brain injury, central nervous system disorders, and various types of cancer. In this study, we present the cryo-electron microscopy structure of the cysteinyl leukotriene D4 (LTD4)-bound human CysLT2R in complex with a Gα q protein, adopting an active conformation at a resolution of 3.15 Å. The structure elucidates a spacious polar pocket designed to accommodate the two branched negative ends of LTD4 and reveals a lateral ligand access route into the orthosteric pocket located on transmembrane domain helix (TM) 4 and 5. Furthermore, our findings highlight the crucial role of transmembrane domain helix 3 in sensing agonist moieties, representing the pivotal mechanism of receptor activation for both CysLT1R and CysLT2R. Collectively, the insights derived from our structural investigation establish a foundation for comprehending CysLT2R activation by its endogenous ligand LTD4, offering a rational basis for the design of drugs targeting CysLT2R.